Effects of seawater ingestion on lactate response to exercise in runners - Pérez-Turpin, Jose Antonio; Trottini, Mario; Chinchilla-Mira, Juan Jose; Cyganik, Weronika (Biology of Sport, 2017)
The aim of this study was to examine the effect of microfiltered and sterilized seawater ingestion on running performance in a hot environment. This cross-over, double-blind randomized trial included 12 experienced male runners. The subjects randomly consumed seawater (SW) or pure water (placebo) in an equivalent amount of 50 ml five minutes prior to running at 40% of their VO2 max for 95.0 ± 18.5 min, at 30°C, until they lost 3% of body weight. Every 20 minutes, a measurement of their body weight was taken and a blood lactate analysis was performed. The concentration of lactate was significantly lower after the running exercise in the SW condition compared to placebo. The results of this study suggest the ergogenic effects of microfiltered and sterilized seawater ingestion on running performance and lactate production.